Enabling collaborative organizational learning (OL) through email system: The socio-technical approach – A case study - Mohamad, Abdul Karim; Sahib, Shahrin; Mohd Yusof, Mokhtar (2008)
Organizational Learning (OL) is about managing knowledge related to the implementation of information system or information and communication technology(IS/ICT) applications for creating such knowledge-based management operation.One of the IS/ICT applications is an electronic mail (email).Email is a communication tool for enabling supportive platform for networked organizational knowledge and intelligence.However, there are still gaps resulted from the email activities such as lack of focus, information overload and spamming, misused and even, abused.Email has failed to provide evidence for promoting OL. A multi perspective of socio-technical approach was adopted to explore the antecedent, behavior and consequences (ABC) of the email users.A survey was done at Universiti Teknikal Melaka (UTEM) and Kolej Yayasan Melaka (KYM) respectively.The results indicate that first, the email users were found to use email effectively for job related purposes, however it was informally shaped by organizational social process.Second, the push nature of the job-related email content has less significance, yet the email threading is still a significant managerial- pulled of job-related connectivity especially between peers.Third, email supports the collaborative working environment but it is not intentionally tailored to OL.